Socjalizacja w płeć kulturową jako czynnik różnicowania możliwości edukacyjnych i marginalizacji = Socialization into gender as a factor of marginalization and differentiation of educational possiblities - Kluczyńska, Urszula (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Nowadays the concept of gender is analysed more often and more widely. Studies on gender touch upon various aspects which have previously been neglected or trifled. Gender is decoded in relation to as well as through many relationships and phenomena including education. It can be suggested that school reduces gender to its biological aspect or, to be more precise, does not go beyond biological differentiation trifling the social description of differences.
Keywords: płeć kulurowa; socjalizacja; edukacja